1980
DOI: 10.1130/mem153-p7
|View full text |Cite
|
Sign up to set email alerts
|

Cordilleran metamorphic core complexes: An overview

Abstract: More than 25 distinctive, isolated metamorphic terranes extend in a narrow, sinuous belt from southern Canada into northwestern Mexico along the axis of the North American Cordillera. Appreciation of these terranes has evolved slowly, and more than half of them have been recognized only since 1970. Growing evidence shows that these metamorphic terranes and related features evolved in part during early to middle Tertiary time (55 to 15 m.y. B.P.), that is, after the Laramide orogeny but before basin-range fault… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
237
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(243 citation statements)
references
References 38 publications
0
237
0
6
Order By: Relevance
“…Studies of metamorphic core complexes (e.g. Malavieille, 1987a,b;Coney, 1980;Hill et al, 1992) show that shallowly dipping gneissic foliations may develop during crustal extension. In such settings, shear fabrics along extensional detachments may overprint subhorizontal flattening foliations (e.g.…”
Section: Origin Of Shallowly Dipping Foliations In Highgrade Gneiss Tmentioning
confidence: 99%
“…Studies of metamorphic core complexes (e.g. Malavieille, 1987a,b;Coney, 1980;Hill et al, 1992) show that shallowly dipping gneissic foliations may develop during crustal extension. In such settings, shear fabrics along extensional detachments may overprint subhorizontal flattening foliations (e.g.…”
Section: Origin Of Shallowly Dipping Foliations In Highgrade Gneiss Tmentioning
confidence: 99%
“…Although it is now widely agreed that core complexes are mainly the product of large-magnitude extension, exactly how core complexes form and evolve over time remains controversial. Perhaps the most contentious features of core complexes are the low-angle normal (detachment) faults that are thought to play a central role in their exhumation [e.g., Coney, 1980]. Many workers have suggested that these faults initiated and slipped at low angles and accumulated tens of km of slip at very high rates [e.g., Reynolds and Spencer, 1985;Davis et al, 1986;John, 1987;Scott and Lister, 1992;Wernicke, 1981Wernicke, , 1985.…”
Section: Introductionmentioning
confidence: 99%
“…[2] In the nearly 4 decades since the recognition of metamorphic core complexes as the product of extensional tectonism, these enigmatic features have played a prominent role in our understanding of both how the crust mechanically extends [e.g., Lister and Davis, 1989;Wernicke, 1992;Axen, 2007] as well as how the North American Cordillera has evolved during the Cenozoic as a whole [e.g., Coney, 1980;Burchfiel et al, 1992]. Although it is now widely agreed that core complexes are mainly the product of large-magnitude extension, exactly how core complexes form and evolve over time remains controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within El Jaralito batholith, Laramide magmatism is represented by dioritic to granitic plutons, including two-mica peraluminous granites, that range in age from ~70 to ~50 Ma (González-León et al, 2011), whereas in its flanks there are Oligocene-Miocene metamorphic core complexes of Sierra Mazatán, Sierra El Jaralito and Sierra Aconchi (Coney, 1980;Anderson et al, 1980;Nourse et al, 1994; Vega-Granillo Figure 1. Digital elevation map (taken from GeoMapApp at www.geomapapp.…”
Section: Introductionmentioning
confidence: 99%